Pengaruh Kombinasi Antara Senam Aerobic Low Impact dengan Diaphragma Breathing Exercise terhadap Tingkat Kebugaran pada Lansia di Komunitas Lansia Malang - Wardhani, Ajeng Dyah Ayu Pramudya; Yuliadarwati, Nungki Marlian; Multazam, Ali (NHM PRESS, 2024)
Aging is a stage of life that is accompanied by structural and functional decline in the body's organs, which has an impact on fitness levels. Aerobic low impact exercise and diaphragm breathing exercise are designed as exercises that aim to improve fitness. The purpose of this research was to examine the effects of combining aerobic low impact exercise with diaphragm breathing exercises on fitness levels of the elderly at the Malang Elderly Community. The study followed a pre-experimental design, employing a one group pretest-posttest approach without a control group. 38 elderly participants were involved in the exercise program, which consisted of 12 sessions, each lasting 45 minutes and conducted every other day. Elderly fitness was measured using the 2 minute walking test (2MWT). Using a paired t-test, the data anlysis revealed a significant p-value of <.001, which is smaller than 0.05, indicating that the combination of aerobic low impact exercise with diaphragm breathing exercises significantly affects fitness levels in the elderly at the Malang Elderly Community.